ANALISIS KUALITAS AIR DAN CEMARAN LOGAM BERAT MERKURI (Hg) DAN TIMBAL (Pb) PADA IKAN DI KANAL DAERAH HERTASNING KOTA MAKASSAR - Wanna, Manna; Yanto, Subari; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
This study aims to determine the quality of canal water as well as to know the presence or absence of heavy metal contamination of Hg and Pb in fish derived from the canal. The research method is descriptive quantitative. Water testing conducted at BBIHP Makasaar with parameters DO, BOD, COD, Hg, and Pb as well as testing the type of tilapia fish and sepat Siam conducted in BPPMHP Makassar with heavy metal parameters Hg and Pb. The length of the canal (Gowa canal) is about 2.95 km. The results showed that the water quality of Hertasning canal in good condition when viewed from pH, DO and COD parameters because it is still in the range of water quality standard class III according to PP RI. 82 of 2001 except BOD parameters. Water and fish derived from the Hertasning canal have contained heavy metal contamination of Hg and Pb. The results showed that the concentration value of heavy metals Hg and Pb is well below the threshold set according to PP RI. 82 year 2001 so that still can be utilized according to its allotment. The content of heavy metals Hg and Pb in both types of fish is also still below the threshold set by SNI 2729: 2013 for fresh fish.